KESIAPAN INSTITUSI PELAKSANA DALAM IMPLEMENTASI PROGRAM INDONESIA PINTAR (PIP) UNTUK TINGKAT SEKOLAH MENENGAH ATAS (SMA) DI WILAYAH JAKARTA SELATAN - Vivie Haryanti (Sekolah Pascasarjana UNAS, 2016)
This study aims to understand the readiness of the implementing agencies in implementing the Indonesia Pintar program for poor student. The method used in this study is a qualitative method. Data collection techniques using interview, observation and documentation. The research findings show that, in the implementation of PIP, not a mutual coordination and cooperation of several institutions, especially at the beginning of the program. Institutions under the Ministry do not know the extent of the development of the program. Bureaucratic structure was not built in accordance with requirements of existing jobs. Yet to realize a program have to prepare all the necessary things such as: budget and organizational structure of the program implementers. This volatility could be political pressure that eventually becomes a factor inhibiting of PIP. The future is expected that existing barriers can be minimized so that PIP may be better in practice.Keywords: Institutional development